(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to examine the effectiveness of two training methods, step receive and table bounce, in improving the first-ball receive ability of sepak takraw athletes in PSTI Kudus Regency. Using a quantitative experimental approach with a two-group pretest-posttest design, the study involved 20 male athletes aged 13–18 years, divided into two experimental groups and one control group. The experimental groups underwent 16 training sessions over four weeks, while the control group received no intervention. Data were collected through skill tests and analyzed using paired sample t-tests in SPSS. The results showed significant improvements in receiving skills: the step receive method increased performance by 38.72%, and the table bounce method by 30.77%, whereas the control group showed no significant change. These findings indicate that both methods are effective, with the step-receive method having a greater impact. This study highlights the importance of varied training techniques in enhancing athletes’ technical skills and provides practical recommendations for coaches and players to optimize training programs.